Total Quality Management and Organisational Performance (British Journal of Multidisciplinary and Advanced Studies, 2024)
The purpose of this study is to evaluate the impact of TQM on organisational performance at First Bank Plc from 2010-2019, data were sourced through secondary means from the bank and annual financial report of the bank for the years2010-2019) and staff of the bank in Ondo state based on Senatorial District in the state. Questionnaire was designed and data collected using 5-Point Likert-Scale questionnaire which was administered on sample of 196 respondents comprises of bank staff, management and customers at the bank in three Senatorial District of the state. The data was analyzed using descriptive statistic in line with graph, Regression Statistical Technique. Five hypotheses formulated were tested using Eview9 at 0.05(5%) level of significance respectively. Findings divulge that there is a significant relationship between all selected variables of employment involvement team work and trust on first bank non-financial performance at (0.090